Effectiveness of Using Ludo Game-Based Learning Media to Improve Understanding of Spatial Building Concepts in Elementary School Students: Literature Review - Rahmawati Rizqiyani; Nurbaetullah Karnita; Wardatun Laela; Kunia Wati; Rasilah Rasilah (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Understanding the concept of spatial structures is a significant challenge in elementary school mathematics education due to its abstract nature. This study aims to evaluate the effectiveness of Ludo game-based learning media in enhancing students' understanding of spatial concepts. This research uses a literature review method to analyze various previous studies using game-based media to teach spatial concepts. The findings indicate that Ludo games significantly improve students’ cognitive understanding by visualizing abstract concepts more concretely, fostering active and interactive learning, and reinforcing concepts through repetition. Additionally, this medium enhances students' learning motivation and spatial skills. However, its implementation faces challenges, such as diverse student abilities, limited classroom time, and the need for teacher training to integrate the games into the curriculum. These findings highlight the substantial potential of Ludo games in addressing difficulties in mathematics education, particularly in understanding spatial concepts. This study recommends integrating game-based media into teaching strategies to create a more engaging and effective learning environment.